'Hard' crystalline lattice in the Weyl semimetal NbAs. (14th January 2016) - Luo, Yongkang; Ghimire, N J; Bauer, E D; Thompson, J D; Ronning, F
Abstract: We report the effect of hydrostatic pressure on the magnetotransport properties of the Weyl semimetal NbAs. Subtle changes can be seen in the profiles with pressure up to 2.31 GPa. The Fermi surfaces undergo an anisotropic evolution under pressure: the extremal areas slightly increase in the - plane, but decrease in the - ( ) plane. The topological features of the two pockets observed at atmospheric pressure, however, remain unchanged at 2.31 GPa. No superconductivity can be seen down to 0.3 K for all the pressures measured. By fitting the temperature dependence of specific heat to the Debye model, we obtain a small Sommerfeld coefficient mJ (mol·K 2 ) −1 and a large Debye temperature, K, confirming a 'hard' crystalline lattice that is stable under pressure. We also studied the Kadowaki–Woods ratio of this low-carrier-density massless system, cm mol 2 K 2 J −2 . After accounting for the small carrier density in NbAs, this indicates a suppressed transport scattering rate relative to other metals.